Access to social security for digital platform workers in Germany and in Russia: a comparative study - Chesalina, Olga (SPANISH LABOUR LAW AND EMPLOYMENT RELATIONS JOURNAL, 2018)
A common feature of platform work in Germany and Russia is that in both countries the new forms of employment can usually only be classified as self-employed work in the form of ‘solo self-employment’, despite the fact that platforms use direct and indirect control mechanisms indicating a personal or at least an economic dependency of the digital workers on the platforms. The difference is that, in Germany, as the main rule, self-employed persons are not obligatorily insured in the state pesion insurance scheme, whereas in Russia, unlike Germany, the state pension insurance scheme is mandatory for all self-employed persons. Considering the different legal frameworks in Germany and in Russia, the article analyses various reform proposals aiming at tackling the above-mentioned challenges for the social security systems, and looks for adequate responses to ensure access to social security for digital platform workers. In particular, the following questions are investigated: Is it sufficient to subsume digital work under the existing employment categories? Could it be an appropriate solution for the access of digital workers to social security to introduce a new employment category only in social law?